Ethical issues when using statistical analysis in research - Daoud, Jamal Ibrahim; Azram, Mohammad (2013)
Ethics and regulations are rules written or agreed upon to implement a certain activity so that no harm can occur to any party involved or not involved in this activity. It seems that when there is any violation to any party, then it is an unethical issue. In fact, in scientific research, it is not necessary that there is second or third party can be violated, but using the analysis tools and related behaviour should be ethical. Ethical matters should be the concern of the researcher himself because sometimes there will be an unethical behaviour but not be known by others. Should we consider any result obtained or any analysis tool which used not ethically ethical as long as no body except the researcher knows about it. These are some issues to be discussed in this paper, other matter as well.